Production, characterization and application of cellulose fibers and nanofibrils and its classification by near infrared spectroscopy - Costa, Lívia Ribeiro (2021)
The existence of alternative, reliable and effective methods for characterization of cellulose fibers and nanofibrils allows industrial processes to be optimized. The evaluation of the consistency of cellulose pulps, the quality of nanofibrils and the application of these materials in paper are relevant subjects to be studied. Studies have indicated that spectroscopic techniques are promising tools for the characterization of nanofibrils, especially in the solid state. However, the characterization of cellulosic fibers/nanofibrils in aqueous media is still a challenge in the spectrometric area. Thus, the aim of this study was to develop a fast and reliable solution based on spectroscopic techniques for evaluating the properties of cellulose fibers and nanofibrils and also to develop new papers using the mixture of these cellulosic materials. For this, this study was divided into two parts, the first part presenting the theoretical framework together with the general considerations of the thesis and the second part presents the articles that support the thesis. In the first article, regressions and artificial neural networks to estimate the solids content of cellulose pulps were developed based on near infrared (NIR) spectra (Article 1, published). The second article is dedicated to the evaluation of cellulose nanofibrils in suspension to estimate the quality of this material through NIR spectroscopy (Article 2). The third article aimed to evaluate the physical and mechanical performance of paper sheets with the addition of different proportions of nanofibrils (Article 3, published). The results indicated that the NIR technique has great potential for evaluating cellulose fibers and nanofibrils quickly and reliably. Furthermore, it is concluded that nanofibrils had a relevant effect on the physical and mechanical properties of the papers produced.